2002
DOI: 10.1111/0022-1082.00485
|View full text |Cite
|
Sign up to set email alerts
|

Global Diversification, Industrial Diversification, and Firm Value

Abstract: Using a sample of 44,288 firm-years between 1984 and 1997, we document an increase in the extent of global diversification over time. This trend does not ref lect a substitution of global for industrial diversification. We also find that global diversification results in average valuation discounts of approximately the same magnitude as those for industrial diversification. Analysis of the changes in excess value associated with changes in diversification reveals that increases in global diversification reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
558
5
17

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 837 publications
(628 citation statements)
references
References 50 publications
48
558
5
17
Order By: Relevance
“…Directors have greater freedom to pursue strategies that are not always consistent with the objective of maximizing shareholder wealth. These results are confirmed by more recent study by Denis et al (2002) on international diversification. This relationship also exists in the case where the protection of shareholders' interests is low .…”
Section: Entrenchement Behavior Manager Ownership and Diversificationsupporting
confidence: 88%
“…Directors have greater freedom to pursue strategies that are not always consistent with the objective of maximizing shareholder wealth. These results are confirmed by more recent study by Denis et al (2002) on international diversification. This relationship also exists in the case where the protection of shareholders' interests is low .…”
Section: Entrenchement Behavior Manager Ownership and Diversificationsupporting
confidence: 88%
“…In other words, if the target and the acquirer belong to the same industry, operational and financial synergies are more likely to be achieved in the cross-border M&As. Many studies have confirmed that a higher abnormal return is reported for related acquisitions than non-related ones (Akbulut & Matsusaka, 2010;Denis, Denis, & Yost, 2002;Moeller & Schlingemann, 2005;Slangen, 2006).…”
Section: Industry Relatednessmentioning
confidence: 87%
“…We extend the analysis by additionally including the geographic dimension of diversification (e.g., see Denis, Denis, and Yost, 2002) and testing some peculiarities associated with diversification such as the existence of "too big to fail" guarantees. We also account for the endogeneity of the diversification decision in our econometric analysis.…”
Section: Literature Reviewmentioning
confidence: 99%